A nova cara da beleza: comunicação & consumo de ativismo na estratégia discursiva da L’Oréal no Instagram - Fischer, Giovanna Masiero (2024)
This research aims to investigate the discursive calls to consumer activisms in the promotional communication of L´Oréal brand in Instagram platform. The main objective is to understand the configurations of discursive strategies in the brand while designing its storytelling, seeking to describe and comprehend the interfaces between consumption and activism in the beauty and personal care market, discussing the relationships and implications of the theme under different perspectives, such as representation processes, identity, and consumer activism in a neoliberal market context. The methodology of this study is Maingueneau (2015) discourse analysis to evaluate the ad creatives of the brand on the social media platform, looking to enhance the understanding of the most used strategies on the period from July 24 to August 21, 2024. L´Oreal can be considerate the global leader brand in the beauty market and is repositioning its discursive ethos from a construction of a rearticulated narrative, that not only includes new body and causes representations on ad creatives, but also reallocates it as an inclusive company to work, at the same time that it maintains the signs of symbolic imaginary of luxury in its ads that has been developed historically over the more than 100 years of brand existence. In rearticulating in new representations of body and causes, the company also introduces behavioural aspects in its ad creatives and introduces elements of advocacy advertising as a fundamental part of its communication strategy. As such, we conclude that behaviours such as empowerment, entrepreneurship and possible futures are presented recurrently, calling the consumers to an experience of behavioural change that are connected to the consumption of the products from the brand.